Pengaruh Beban Kerja, Disiplin Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT Volex - Nani Hartati Sihotang; Asron Saputra (Komunitas Dosen Indonesia, 2024)
This study aims to analyze the effect of workload, work discipline, and job satisfaction on employee performance at PT Volex. The type of research used is descriptive with a quantitative approach. The population used is all employees who work as production operators in the ICA department at PT Volex in 2023 with a total of 112 employees with sampling based on saturated sampling, using a questionnaire distributed to PT Volex employees. The collected data were analyzed using multiple linear regression methods which were tested involving data quality tests, classic assumption tests, influence tests and hypothesis tests, to determine the effect of workload, work discipline, and job satisfaction variables on employee performance. Findings in multiple linear regression analysis can show that workload has a positive relationship with a magnitude of 26.2% on employee performance. Work discipline has a positive relationship with a magnitude of 21.2% on employee performance. Job satisfaction has a positive relationship with a magnitude of 34.1% on employee performance. The findings of the analysis of the coefficient of determination (R2) that the level of employee performance can be explained by workload, work discipline and job satisfaction of 72.5%. The research results in the hypothesis testing carried out can show that workload, work discipline and job satisfaction partially or simultaneously can provide a positive and significant relationship to employee performance.